Perumusan Stategi Bisnis dengan Pendekatan "Game Theory" - Noorida, Titik (Jurnal Teknik Industri, 2000)
The increase or the Merck and kind of cigarette that revolve in the market had caused  a competition in the cigarette tighter. The new Werck that enter the market hardly fight to get the market segment with looking for another Merck's consumer, while the Merc's that had a name in the market for along time must retained to be dead increase their market section or just keep on the market segment that possess it. In the other hand,  government always suggests the  society not to smoking because of helath reason.  This matter, of course little or more influence the growth of cigarette  consumption that  at the  end will make tighter  the  cigarette product  competition  the market. The enterprises that is involved in the competition condition of course will not released from importance of the strategy utilizing optimally so the pproduct that sold will stand survive The tighten of this competition require the cigarette producer to be creative in looking  for the marketing strategy that fit to the product wich risen. One of them is with  do the  competition analysis.  This competition analysis function as to know the speciorities and weakness that is had by main competitors. Beside that enterprise also must be able to catch consumer preference in the aim to consume the cigarette also their perception to the product is risenProduct grouping is done to know the main competitors Pall Mall product from the product grouping that  is done.  It's  found that  Pall Mall tightly compete with  Sampoerna A Medium, Wismilak,  Diplomat,   234  Filter,   and   Gudang  Garam  Internasional   Merah   Analysis,   the competition is made with that main competitor. It so happens the mathod that is used for analyze that competition is Game Theory Method which is used is Two Person Non Zero Sume  Game and finished with linear program simplex mathod.  The result that is get in this competition analysis is competitions speciorities which is had by product compared with main competitor.The main purpose from the whole calculation and the data processing is business  strategy formulation  optimally  based  on  speciorities that  is  had  by  product  with  consider   about the speciorities of the main competitor also consumer preference. Formulation will be made specially to the Pall  Mall product with the main competitors.  The prime thing that is a grip in the business stratefy formulation is the speciorities that's had by main competitors and consumer preference to the p~oduct attributes.